The Free and Open Indo-Pacific and Implications for ASEAN. - Lee, John (ISEAS - Yusof Ishak Institute, 2018)
In recent times, the United States, Japan and Australia have all promoted extremely similar visions of a Free and Open Indo-Pacific as the central organizing concept to guide their efforts in the region. The concept is essentially a reaffirmation of the security and economic rules-based order which was cobbled together after the Second World War -- especially as it relates to freedom of the regional and global commons such as sea, air and cyberspace, and the way nations conduct economic relations. Be that as it may, the Free and Open Indo-Pacific is an updated vision of collective action to def.